Diseño y ejecución de una consultora que capacite y oriente en la exportación de productos no tradicionales, a pequeños y medianos agricultores, caso tipo la uvilla Ecuatoriana - Ortiz Godoy, Xavier Aurelio (2008)
To propose a consultancy dedicated to providing services to the benefits to farmers of nontraditional products, identifying the competitive aspects and management can have on the domestic and foreign markets. To improve their productive capacity and economic benefits.